Select Correspondence of Ronald Syme, 1927-1939 [History of Classical Scholarship] - Gago, Mikel (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
Birley, A. R. (ed.), Select Correspondence of Ronald Syme, 1927-1939 [History of Classical Scholarship, Supplementary Volume 1], Newcastle Upon Tyne-Venezia, 2020, 211 págs., ISBN 9781838001803 [Reseña]